Why young people with eating disorder symptoms do not seek help: exploring barriers to help-seeking - Stadler, Johanna; Moessner, Markus; Seidel, Katja; Hiery, Alisa; Diestelkamp, Silke; Eschenbeck, Heike; Gillé, Vera; Kaess, Michael; Koenig, Julian; Rummel-Kluge, Christine; Kohls, Elisabeth; Thomasius, Rainer; et al. (The international journal of eating disorders, 2025)
Objective Rates of help-seeking and treatment uptake are low in eating disorders. Delayed initiation of treatment has a negative impact on prognosis and treatment outcome and leads to a higher burden on the healthcare system. The aim of this study was to explore factors associated with help-seeking and their interactions in a large sample of adolescents and young adults with current symptoms of an eating disorder. Methods Based on the Classification and Regression Trees (CART) algorithm, the data collected within the German school-based project ProHEAD (N = 9796; age: 12-25 years) were used to estimate a decision tree to classify students into help-seekers and non-help-seekers for a mental health issue. Results Of those screened, 13% reported substantial current eating disorder symptoms (N = 1273). Out of those, 77.3% reported that they did not seek formal help (i.e., from a mental health professional). The absence of suicidal ideation and emotional problems, as well as a low level of education and openness to mental health issues, was characteristic of those who did not seek help for a mental health problem. Emotional problems, suicidality, and depressive symptoms were identified as the most important factors associated with general help-seeking. Discussion In line with previous research, our findings indicate that individuals with eating disorder symptoms are more likely to seek help when other mental health issues are present. Public health efforts should aim to promote awareness and increase knowledge of eating disorders.
Gesehen am 30.10.2025